Cytokine-Like 1 is a novel proangiogenic factor secreted by and mediating functions of endothelial progenitor cells - Schneller, Doris; Kapel, Stephanie; Besemfelder, Eva; Augustin, Hellmut (Circulation research, 2019)
Rationale:Endothelial colony forming cells (ECFCs) or late blood outgrowth endothelial cells can be isolated from human cord or peripheral blood, display properties of endothelial progenitors, home into ischemic tissues and support neovascularization in ischemic disease models.Objective:To assess the functions of CYTL1 (cytokine-like 1), a factor we found preferentially produced by ECFCs, in regard of vessel formation.Methods and Results:We show by transcriptomic analysis that ECFCs are distinguished from endothelial cells of the vessel wall by production of high amounts of CYTL1. Modulation of expression demonstrates that the factor confers increased angiogenic sprouting capabilities to ECFCs and can also trigger sprouting of mature endothelial cells. The data further display that CYTL1 can be induced by hypoxia and that it functions largely independent of VEGF-A (vascular endothelial growth factor-A). By recombinant production of CYTL1 we confirm that the peptide is indeed a strong proangiogenic factor and induces sprouting in cellular assays and functional vessel formation in animal models comparable to VEGF-A. Mass spectroscopy corroborates that CYTL1 is specifically O-glycosylated on 2 neighboring threonines in the C-terminal part and this modification is important for its proangiogenic bioactivity. Further analyses show that the factor does not upregulate proinflammatory genes and strongly induces several metallothionein genes encoding anti-inflammatory and antiapoptotic proteins.Conclusions:We conclude that CYTL1 can mediate proangiogenic functions ascribed to endothelial progenitors such as ECFCs in vivo and may be a candidate to support vessel formation and tissue regeneration in ischemic pathologies.
Originally published: October 26, 2018
Gesehen am 14.08.2019